Evaluating Special Educators Knowledge of High Leverage Practices: Finding a High-Leverage Rubric - Smith, Emily; Brezenski, Pamela; Broderick, Jessica; Cavitt, Dennis (Journal of the American Academy of Special Education Professionals, 2024)
Special Education teachers are often held to the same accountability standards as general education standards when it comes to effective teaching. This can cause frustration and disconnect between professionals and their job description. A set of research-based, high-leverage practices has been developed to provide special education teachers with guidance as to what makes them an effective teacher. While the use of high-leverage practices has been accepted and implemented into many districts for teacher effectiveness, special educators need more systematic methods for evaluating the effectiveness of their practice using high-leverage practices. The purpose of this study was to create a tool for administrators to use in providing direct, content level guidance related to high-leverage practices. The purpose of this study was to create a tool through the use of the recommended high-leverage practices that can be used to adequately evaluate special educators’ performance in the classroom and the inclusive setting.